PENGARUH MEDIA BONEKA WAYANG KARDUS TERHADAP KEMAMPUAN BERCERITA ANAK - fauziah, anisa'ul (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2019)
This research is motivated by the story-telling ability for language development are designed to develop the potential of communication and vocabulary expansion. Through stories, children receive proper example of how to speak, asked for help, thank you, and defend themselves. Based on this, the media â€œWayang Kardusâ€ used as an alternative in learning. This study aims to determine the effect of the Media Wayang Kardus on Storytelling Ability of Studentâ€™s Group B TK Sartiasari Wonorejo Surabaya. Indirectly storytelling can improve their language skills. This study is a One-Group Pretest-posttes Design. Results showed before and after exercise there is increased development of language skills of children in group B TK Sartiasari Surabaya. The results show the data t = (23.117) is greater than t table = (2.042) with a significance level of 5%. which means there is significant influence between Media Wayang Kardus on Storytelling Ability of children Group B TK Sartiasari Wonorejo Surabaya. Media Wayang Kardus Influential on Storytelling Ability of Children Group B TK Sartiasari Wonorejo Surabaya.